Mechanisms of c-Fos regulation of mTOR signaling via ERα/β in abnormal lipid metabolism of granulosa cells in PCOS - Chen, Xinyi; Shen, Xiaoxue; Guan, Shanyue; Liu, Yan; Song, Ning; Song, Wenyan; Jin, Haixia (Frontiers in Endocrinology, 2025)
ObjectiveThis study investigates the role of the c-Fos/estrogen receptors (ERs)/mTOR pathway in lipid metabolism in human follicular granulosa cells of individuals with polycystic ovary syndrome (PCOS). Specifically, we aim to determine whether c-Fos targets estrogen receptors (ERα and ERβ) to mediate the mTOR pathway, influencing lipid metabolism, and to identify the key molecular mechanisms involved.MethodsA PCOS mouse model was established using dehydroepiandrosterone (DHEA), and ovarian tissues were collected from both PCOS and control mice. RT-qPCR and Western blotting were used to measure the expression levels of c-Fos, ERα, ERβ, and mTOR. Follicular fluids were obtained from patients with PCOS and male factor infertility on the day of ovulation. Adenovirus-mediated upregulation of c-Fos was performed in human follicular granulosa cells from male infertility patients, followed by analysis of mRNA and protein levels of c-Fos, ERα, ERβ, and mTOR. Additionally, granulosa cells’ triglyceride (TG) and total cholesterol (TC) levels were assessed. Granulosa cells were cocultured with various concentrations of 17β-estradiol to investigate the effects of estrogen on the pathway.ResultsIn ovarian tissues of PCOS mice, mRNA and protein levels of c-Fos were significantly elevated compared to controls, while ERα and ERβ expression was notably reduced. No significant changes were observed in the p-mTOR/mTOR protein ratio. In PCOS patients, c-Fos and p-mTOR/mTOR protein levels were higher than in male factor infertility patients, while ERα levels were lower, with no significant difference in ERβ expression between the two groups. Upregulation of c-Fos in human granulosa cells led to a significant reduction in ERα and ERβ levels, while p-mTOR/mTOR protein levels increased. TG content was elevated in the c-Fos-upregulated group compared to controls, but no significant changes were observed in TC levels. Co-culture of granulosa cells with increasing concentrations of 17β-estradiol resulted in significantly higher ERα and ERβ expression, decreased p-mTOR/mTOR levels, and a reduction in TG content, while TC levels remained unchanged.ConclusionsThese findings suggest that c-Fos may target ERα and ERβ to mediate the mTOR signaling pathway, thereby influencing lipid metabolism in granulosa cells. This novel mechanism provides insights into potential therapeutic strategies for managing PCOS-related metabolic dysfunction.